Prensa e imperialismo popular. La Vanguardia y el lobby africanista a finales del siglo XIX - Pol Dalmau (Cahiers de Civilisation Espagnole Contemporaine)
The purpose of this article is to study the relationship between the emergence of a new commercial and mass press and the promotion of Spanish colonialism in Morocco at the end of the 19th century. To do so, it focuses on the case of La Vanguardia, a newspaper that is as well-known as it is little studied by historians. Originally founded as a party newspaper, in 1888 the Godó family promoted a radical change in the editorial line of La Vanguardia in order to expand its readership and increase its influence. Under a new guise as an informative and business newspaper, La Vanguardia climbed the ranks to become the best-selling daily in Barcelona, while at the same time becoming the main spokesman for Africanist interests in Catalonia. The case of this newspaper offers the opportunity to study the relations between the press and lobbies, as well as examine the public dimension of issues such as imperialism and national identities. To address all these questions, we will focus on the Melilla War of 1893, a short-lived conflict that sparked strong popular mobilization.